Ti3C2Tx MXene embedded metal–organic framework-based porous electrospun carbon nanofibers as a freestanding electrode for supercapacitors. Issue 10 (14th February 2023) - Pathak, Ishwor; Acharya, Debendra; Chhetri, Kisan; Chandra Lohani, Prakash; Subedi, Subhangi; Muthurasu, Alagan; Kim, Taewoo; Ko, Tae Hoon; Dahal, Bipeen; Kim, Hak Yong
Abstract : Ti3 C2 T x MXene-integrated porous carbon nanofiber freestanding/flexible electrodes are engineered and the optimized MX-5@PCNF is used for the fabrication of flexible symmetric and asymmetric supercapacitor devices with high energy density. Abstract : Rational modification of Ti3 C2 T x MXenes for the preparation of freestanding and flexible carbon-based electrodes with great prospects for an energy storage facility is a crucial task for new-generation supercapacitors. Herein, a novel Ti3 C2 T x MXene-decorated porous carbon nanofiber (PCNF) freestanding/flexible electrode is engineered through a sequential approach of electrospinning, in situ growth of ZIF67, and a carbonization process. By varying the concentration of MXenes in the fiber, the electrochemical performance of a set of MXene-integrated PCNFs is investigated, and flexible symmetric and asymmetric supercapacitor devices are assembled. The optimized MX-5@PCNF achieves a specific capacitance of 572.7 F g −1 at 1 A g −1 with high cycling stability (96.4% capacitance retention after 10 000 cycles) and superior rate capability (71.24% at 30 A g −1 ). Furthermore, MX-5@PCNF-based flexible symmetric and asymmetric (Co3 O4 @NF//MX-5@PCNF) devices furnish high energy densities of 22.53 W h kg −1 and 74.2 W h kg −1, respectively, along with a long life cycle, ideal coulombic efficiency, and rate capability, demonstrating their practical applicability. This study provides an alternative strategy to prepare MXene-decorated PCNF freestanding electrodes with high performance, and the technique can be extended to other 2D MXenes for designing efficient electrodes for flexible supercapacitors.